True North Research directors reveal how sport sponsorship changed during COVID-19 - Hodson, J. (Ministry of Sport, 2021)
Speaking to Ministry of Sport, True North Research directors, Georgie Maynard, and Chris Hobden, reflected on how COVID-19 has changed the Australian sport sponsorship market through 2020.